Ambient vibration testing and analysis of a single-span bridge - Leong, Winnie Phei Wen (Nanyang Technological University, 2021)
Ambient vibration testing has been used to determine modal parameters of civil engineering structures in the recent years. The advantage of this technique is that no forced excitation needs to be applied to the structure and is generally safe. The proposed project is to conduct ambient vibration testing on a single-span bridge. The primary working principle of this project to collect ambient data from the North Spine footbridge and use the MATLAB software to analyse the response and power spectral densities of the data to obtain the dynamic properties of the structure, namely the natural frequencies, damping ratios and mode shapes of the structure. The dynamic properties will allow one to assess the serviceability of a structure for consumer use.